Andragogical methodologies: a PIBID experience report in Youth and Adult Education - Milena Souza da Silva; Flávia Rosa dos Santos; Édila Dalmaso Coswosk (Universidade Federal do Oeste da Bahia, 2021)
This work aims to report the experience of the development of andragogical methodologies applied in the Youth and Adult Education (EJA) modality by graduates in Biological Sciences / scholarship holders of the Institutional Program for Teaching Initiation Scholarships (PIBID) of the State University of Bahia- Campus X. EJA's Curricular proposal aims at equity in access to education and andragogical methodologies, based on the understanding of the student as an adult and their specificities in relation to learning and acquiring new knowledge of interest. The experiences in the school space constitute a teaching laboratory, being necessary to articulate contents of the natural sciences with the pedagogical ones studied during the course, in addition to dealing with the difficulties of interpersonal relationships. In this experience, an additional conflict was that the specificities of EJA are not discussed in the pedagogical components of the undergraduate course.